123 Review of patients known to community specialist palliative care team that are admitted to Dudley Group of Hospitals NHS FT. (14th March 2023) - Bowen, Joanne; Hall, Kate; Cowdell, Nadine
Abstract : Introduction: The Specialist Palliative Care team in Dudley is an integrated team and therefore, when patients known to the team are admitted to Russells Hall Hospital an email alert is triggered that the hospital team can process. Approximately 50% of the patients on the hospital caseload are patients known to the community part of the integrated team. Therefore, a review of these admissions was planned to identify any themes to improve patient outcomes. Method: Review of March 2022 patients on the hospital caseload using proforma to capture information including diagnosis, reason for admission and if admission was organised by the specialist palliative care team. Results: In March 2022 there were 24 admissions to Russells Hall Hospital for 19 patients known to the community team. Two patients had 3 admissions and 1 patient 2 admissions. Most patients had a cancer diagnosis. With regards to the admissions 5 were arranged by the community specialist palliative care team. The admissions were for a range of reasons including possible malignant spinal cord compression, chemotherapy side effects, symptoms including pain, nausea and vomiting and breathlessness that required further investigation. The minimum a patient should be seen in community known to the specialist palliative care team is monthly and of the admissions only 1 patient had not been seen within a month of admission. Discussion: With the caseload held by the hospital team having approximately 50% of patients known to the community team this review has provided assurance that admissions were appropriate. Next steps include a review of criteria for prioritisation of patients either known to the integrated team or ward referrals and criteria for minimum number of visits including consideration of phase of illness supporting the need of specialist input.